Intravenous Tezosentan and Vardenafil attenuate acute hypoxic pulmonary hypertension - Geiger, R.; Treml, B.; Kleinsasser, A.; Neu, N.; Fischer, V.; Stein, J. I.; Loeckinger, A. (High Altitude Medicine & Biology, 2008)
Excessive hypoxic pulmonary hypertension imposes right ventricular strain by increasing afterload that may lead to right heart failure and death. Increased phosphodiesterase activity, as well as increased levels of endothelin-1, has been discussed as molecular mechanisms. We investigated the hemodynamic and intrapulmonary effects of the intravenous dual endothelin A and B receptor blocker tezosentan, and of the phosphodiesterase-5 (PDE-5) antagonist vardenafil in a pig model of acute normobaric hypoxic pulmonary hypertension. Eighteen 4-week-old ventilated white farm pigs were exposed to normobaric hypoxia (FiO2 12%) and randomly assigned to three groups (n = 6) in order to receive either intravenous tezosentan or vardenafil or to serve as control. Arterial alveolar oxygen differences were the same with both drugs. After 90 min of treatment, pulmonary artery pressure and vascular resistance were significantly lower in both treatment groups when compared to controls (p < 0.001). Cardiac index increased significantly with vardenafil alone (2.8 l · min-1 · m2 ± 0.7 to 4.2 l · min · m2 ± 0.7, p = 0.0003). Intravenous tezosentan, as well as vardenafil equipotently attenuate acute hypoxic pulmonary hypertension without afflicting pulmonary gas exchange. However, cardiac index increases with vardenafil only.